2019
DOI: 10.48550/arxiv.1903.09969
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Asymptotic properties of steady and nonsteady solutions to the 2D Navier-Stokes equations with finite generalized Dirichlet integral

Abstract: We consider the stationary and non-stationary Navier-Stokes equations in the whole plane R 2 and in the exterior domain outside of the large circle. The solution v is handled in the class with ∇v ∈ L q for q ≥ 2. Since we deal with the case q ≥ 2, our class is larger in the sense of spacial decay at infinity than that of the finite Dirichlet integral, i.e., for q = 2 where a number of results such as asymptotic behavior of solutions have been observed.For the stationary problem we shall show that ω(x) = o(|x|2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…which has characteristic equation (8). Case 2.1: If δ > 0, equation (8) has two different real roots m, n (m > n) and the general solution of ( 13) is expressed as follows…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…which has characteristic equation (8). Case 2.1: If δ > 0, equation (8) has two different real roots m, n (m > n) and the general solution of ( 13) is expressed as follows…”
Section: Preliminariesmentioning
confidence: 99%
“…where λ ± µi (µ = 0) are the complex roots of equation (8). Since ϕ 1 and ϕ 2 are linearly independent, then C 2 1 + C 2 2 = 0. ϕ 1 , ϕ 2 ∈ C 0 at r = 0, then k = λ > 0.…”
Section: This Equation Has General Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…See also [1,14] for some related improvements. Recently Kozono-Terasawa-Wakasugi [18] showed that solutions of (1.1) in 2D space with (1.2) (2 < q < +∞) satisfy a priori estimates u(x) = o(|x| 1−2/q ) and w(x) = o(|x|…”
Section: Introductionmentioning
confidence: 99%